A Comparative Analysis of Source and Target Cultures in Indonesian 10th Grade English Textbooks - Anggraini, Dilla; Rohmah, Zuliati (International Journal of Language Teaching and Education, 2024)
This study examines cultural representation in two Indonesian grade 10 English textbooks, Bahasa Inggris "Work in Progress" and Pathway to English, within the context of the new Merdeka curriculum. It aims to explore differences in cultural content between the source culture (Indonesia) and the target culture (English-speaking countries) using Yuen’s (2011) content analysis framework. The findings reveal that Bahasa Inggris "Work in Progress" presents a more balanced portrayal by highlighting the source culture and incorporating international elements, especially through visuals. In contrast, Pathway to English predominantly emphasizes the target culture, offering a limited representation of Indonesian culture. This imbalance may hinder students’ cultural identity development while promoting global awareness. The study highlights the need for more balanced cultural representation in textbook design to enhance students’ cultural competence and suggests further research on how such materials influence students' cultural understanding.